SoC FPGA-Based Rapid Prototyping of Compressed, Secured and Wireless Image Transmission for Wildlife Surveillance System - Mohd Nadzri, Muhamad Muzakkir; Ahmad, Afandi (International Journal of Integrated Engineering, 2022)
Wildlife plays an important role in balancing the earth’s ecosystem. Today, many species of wildlife are threatened with extinction. Images are important input data for wildlife surveillance technology, which allows real situations in the field to be observed and analysed. This project proposed a wireless transmission system of compressed and secured images using the SoC FPGA platform for improving the existing system. Image compression ensured that the proposed system was efficient in terms of data processing, transmission and storage. Image data encryption aimed at ensuring that the security of the transmitted image data would not be hijacked by poachers or non-authorities and ultimately this system would transmit compressed and secured images wirelessly to provide real-time data. The prototype used LabVIEW 2017 software and NI myRIO (as image transmitter) and computer (as image receiver) hardware for the development of the architectural design of a compression system using the discrete cosine transform (DCT) method, the development of an encryption system using the advanced encryption standards (AES) method and wireless transmission using Wi-Fi. The implementation of DCT on the field-programmable gate array (FPGA) platform allowed the images to be compressed by 44% to shorten the time used in the transmission process. AES guaranteed data security with images that can only be viewed when using the correct password. Finally, the rapid prototyping of the wireless transmission of compressed and secured images for the wildlife surveillance system equipped with a motion sensor and a camera was developed to detect motion, capture images and transmit three (3) different image resolutions at distances of up to 60 m.